Educação profissional e relações de gênero: razões de escolha e a discriminação - Almeida, Andréia de (2015)
This work aims to understand how professional choice by students is made, examining also differences and similitudes between men and women searching professional formation and analyzing the existence of discrimination suffered or practiced by men and women in a technical course most frequented by men. Gender relations and professionalization related aspects are focused in this work, which has the Critical Theory of Society as its theoretical ground. Students of the Instituto Federal de Educação, Ciência e Tecnologia de São Paulo industrial automation course, campus Guarulhos, were selected for this research. A questionnaire was applied to a sample of 25 students, 12 women and 13 men. Two hypotheses were considered: I) opinions on work opportunities are the ground from where youngsters justify their choices; besides, their decisions are based on professional and financial success expectations; II) it is possible to observe persistence of discrimination towards women in students sayings regarding areas or careers that are majorly occupied by men. The first hypothesis was partially confirmed as men students point professional and financial success expectations as a reason for studying, but this answer was not the most recurring one. They preferred to point first identification with the area, followed by the possibility of professional ascension, personal satisfaction and course s quality. Women, by their turn, pointed course s quality as their first reason, followed by professional ascension and studies continuity. It could be noted a elaboration of ―being man‖ and ―being woman‖ socially rooted in the responses of the students, and also that this elaboration still drives professional choices and influences the way those choices are made. It was noted as well the persistence of prejudice and discrimination suffered by the women merely by their gender in a course considered ―manly‖